FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA DENGAN PENDEKATAN THEORY PLANNED OF BEHAVIOUR: (Studi Kasus : Mahasiswa Fakultas Ekonomi Universitas Katolik Santo Thomas Medan) - Sitompul, Pandapotan; Silalahi, Esli; Ritonga, Sinar (Jurnal Manajemen dan Bisnis, 2022)
The purpose of this study is to analyze what are the dominant factors that influence student interest in entrepreneurship. The population of this research is all students of the management study program of the Faculty of Economics, Santo Thomas Catholic University who have taken entrepreneurship courses. The sample is 100 students, the method of collecting data is through questionnaires and documentation, the variables studied are about the factors that influence student interest in entrepreneurship, analysis techniques with factor analysis. The results show that, of the 20 factors that influence student interest in entrepreneurship, the most dominant are: The first factor consists of: Leadership, Friends support which is considered important, Friends support, Realistic thinking, Family support and high commitment, Second factor consists of : Have a confident attitude, Foresight, Support business partners, Creative Innovative, Cooperate with business partners and Have experience. The third factor consists of: being disciplined, encouraging parents and being interested in business opportunities. The fourth factor consists of: Courage to face risks. The fifth factor consists of: reliable expertise, perceived ease and careful planning. The sixth factor consists of: Independence. It is better for students during the lecture process to innovate to do a simple type of business as an entrepreneurship learning material. Parents support and motivate their children to become entrepreneurs, because parents have a very strong role in forming entrepreneurial interests. There needs to be an improvement for the campus in providing understanding and training to students so that their entrepreneurial interest is increasingly formed so that after completing their studies their entrepreneurial spirit will be awakened.